FGF9 Alleviates the Fatty Liver Phenotype by Regulating Hepatic Lipid Metabolism - Zhao, Fanrong; Zhang, Lei; Zhang, Menglin; Huang, Jincan; Zhang, Jun; Chang, Yongsheng (Frontiers in Pharmacology, 2022)
Although the fatty liver has been linked to numerous impairments of energy homeostasis, the molecular mechanism responsible for fatty liver development remains largely unknown. In the present study, we show that fibroblast growth factors 9 (FGF9) expression is increased in liver of diet-induced-obese (DIO), db/db and ob/ob mice relative to their respective controls. Long-term knockdown of hepatic FGF9 expression mediated by adeno-associated virus expressing FGF9-specific short hairpin RNA (AAV-shFGF9) aggravated fatty liver phenotype of DIO mice. Consistently, downregulation of FGF9 expression mediated by adenovirus expressing FGF9-specific shRNA (Ad-shFGF9)Ad-shFGF9 in primary hepatocyte promoted the cellular lipid accumulation, suggesting that FGF9 exerts its effects in an autocrine manner. In contrast, adenoviruses expressing FGF9 (Ad-FGF9) mediated FGF9 overexpression in liver of DIO mice alleviated hepatic steatosis, and improved the insulin sensitivity and glucose intolerance. Moreover, the liver-specific FGF9 transgenic mice phenocopied the Ad-FGF9-infected mice. Mechanistically, FGF9 inhibited the expression of genes involved in lipogenesis and increased the expression of genes involved in fatty acid oxidation, thereby reducing cellular lipid accumulation. Thus, targeting FGF9 might be exploited to treat nonalcoholic fatty liver disease (NAFLD) and metabolic syndrome.